Genetic diagnosis and clinical characteristics analysis of cardiospondylocarpofacial syndrome in a Chinese family - Yang, Qi; Zhang, Qiang; Yi, Sheng; Li, Wurui; Zhou, Xunzhao; Zhang, Shujie; Yi, Shang; Zhang, Qinle; Luo, Jingsi (Frontiers in Pediatrics, 2025)
Cardiospondylocarpofacial syndrome (CSCFS) is an extremely rare autosomal dominant disorder resulting from variant in the MAP3K7 gene, which encodes the transforming growth factor-β-activated kinase 1 (TAK1). Only 26 cases of CSCFS have been reported worldwide. The main manifestations are growth retardation, hypotonia, dysmorphic facial features, skeletal and limb abnormalities, cardiac septal defects with valve dysplasia, cardiomyopathy, and deafness with inner ear malformations. In this study, we recruited an unrelated Chinese family with a patient diagnosed with CSCFS. Whole exome sequencing revealed a novel heterozygous variant, c.142G > A[p. (Gly48Arg)], in the MAP3K7 gene. The variant was confirmed by Sanger sequencing to be absent in other family members and is de novo. The patient described here has a similar dysmorphology profile to that associated with CSCFS. Compared with reported cases of CSCFS, our patient presented with new complications of short tongue tie, brain abnormalities including asymmetrical cerebral hemispheres with widening of the right frontotemporal exoptic hiatus, intestinal obstruction and intussusception. In addition, scoliosis, vertebral abnormalities, carpal/tarsal fusion, pectus excavatum, and cervical spine fusion were not found in our patient. The molecular diagnosis in this patient extends the known genetic spectrum of CSCFS. Furthermore, the specific manifestations in this case offer valuable additional clinical details regarding the syndrome.